MuMADS1 and MaOFP1 regulate fruit quality in a tomato ovate mutant. Issue 5 (2nd November 2017) - Liu, Juhua; Zhang, Jing; Wang, Jingyi; Zhang, Jianbin; Miao, Hongxia; Jia, Caihong; Wang, Zhuo; Xu, Biyu; Jin, Zhiqiang
Summary: Fruit ripening and quality are common botanical phenomena that are closely linked and strictly regulated by transcription factors. It was previously discovered that a banana MADS‐box protein named MuMADS1 interacted with an ovate family protein named MaOFP1 to regulate banana fruit ripening. To further investigate the role of MuMADS1 and MaOFP1 in the regulation of fruit quality, a combination of genetic transformation and transcriptional characterization was used. The results indicated that the co‐expression of MuMADS1 and MaOFP1 in the ovate mutant could compensate for fruit shape and inferior qualities relating to fruit firmness, soluble solids and sugar content. The number of differentially expressed genes (DEGs) was 1395 in WT vs. ovate, with 883 up‐regulated and 512 down‐regulated genes, while the numbers of DEGs gradually decreased with the transformation of MuMADS1 and MaOFP1 into ovate. ' Starch and sucrose metabolism' constituted the primary metabolic pathway, and the gene numbers in this pathway were obviously different when MuMADS1 and MaOFP1 were integrated into ovate . A series of metabolic genes involved in cell wall biosynthesis were up‐regulated in the WT vs. ovate, which probably resulted in the firmer texture and lower sugar contents in the ovate fruit. These results demonstrate that MuMADS1 and MaOFP1 are coregulators of fruit quality, facilitating the dissection of the molecular mechanisms underlying fruit quality formation.